Definition of a COPD self-management intervention: International Expert Group consensus. Issue 1 (12th May 2016) - Effing, Tanja W.; Vercoulen, Jan H.; Bourbeau, Jean; Trappenburg, Jaap; Lenferink, Anke; Cafarella, Paul; Coultas, David; Meek, Paula; van der Valk, Paul; Bischoff, Erik W.M.A.; Bucknall, Christine; Dewan, Naresh A.; et al.
There is an urgent need for consensus on what defines a chronic obstructive pulmonary disease (COPD) self-management intervention. We aimed to obtain consensus regarding the conceptual definition of a COPD self-management intervention by engaging an international panel of COPD self-management experts using Delphi technique features and an additional group meeting. In each consensus round the experts were asked to provide feedback on the proposed definition and to score their level of agreement (1=totally disagree; 5=totally agree). The information provided was used to modify the definition for the next consensus round. Thematic analysis was used for free text responses and descriptive statistics were used for agreement scores. In total, 28 experts participated. The consensus round response rate varied randomly over the five rounds (ranging from 48% (n=13) to 85% (n=23)), and mean definition agreement scores increased from 3.8 (round 1) to 4.8 (round 5) with an increasing percentage of experts allocating the highest score of 5 (round 1: 14% (n=3); round 5: 83% (n=19)). In this study we reached consensus regarding a conceptual definition of what should be a COPD self-management intervention, clarifying the requisites for such an intervention. Operationalisation of this conceptual definition in the near future will be an essential next step. Consensus of a conceptual definition of what should be a COPD self-management intervention with its requisites http://ow.ly/Zfr0F